Enhancing Learning Outcomes Rhythmic Gymnastics Learning Model Through Teams Games Tournaments - Martinus (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Physical education, sports, and health are a part of general education that focuses on physical activities as a means of learning. Physical education subjects include games, sports, gymnastics, rhythmic, water activities, and out-of-school education. The purpose to be achieved in this study is to improve the spirit and skills of learners in learning Rhythmic Gymnastics. The method used is Class Action Research or often referred to as action research, where this research will be carried out through several cycles in the hope that there will be an increase in the results to be achieved. The analysis technique used is the percentage to analyze and assessment of the subject of the developer in assessing the level of feasibility, quality and acceptability of the product to the product development. The results showed that the Teams Games Tournaments model can improve students learning outcomes effectively and efficiently, increase students motivation and participation in learning, and improve students  social skills. Conclusion Teams Games Tournaments model in learning rhythmic gymnastics, thereby improving learning outcomes and student motivation and teacher skills in managing learning.